Preparation of a visible light catalyst of novel Bi2WO6 loaded Ag3PO4 heterojunction and its efficient removal of toluene. Issue 1 (31st December 2022) - Zhang, Qi; Zhu, Yuyu; Yu, Liangyun; Dong, Xuexing; Wu, Yifan; Yang, Bairen; Xu, Qi
ABSTRACT: Herein, a novel photocatalyst of Ag3 PO4 /Bi2 WO6 was developed via hydrothermal and precipitation method. Its structure and morphology was characterized through XRD, XPS, SEM, TEM, HRTEM, BET, UV-vis DRS, PL, and so on. By employing toluene photodegradation experiment under visible light, the photocatalytic performance of Ag3 PO4 /Bi2 WO6 was proved to be better than Ag3 PO4 and Bi2 WO6 alone due to the efficient separation of electron-hole pairs. When the molar ratio of Ag3 PO4 to Bi2 WO6 was 1:2, the degradation rate of toluene could reach 80% within 180 min. This study provided a new idea for the simple preparation of cheap and efficient nanocomposite materials for VOCs degradation by visible light.